2016
DOI: 10.14687/ijhs.v13i1.3534
|View full text |Cite
|
Sign up to set email alerts
|

Use of digital books at academic level: Perceptions, attitudes and preferences of post-graduate students

Abstract: Though first appeared in 1971, digital book technology has evolved especially since 2000s and it is relatively a new research area. Therefore, to better understand this phenomenon, a quantitative survey research was conducted in 2015 spring term in a state university in Turkey. The objective of the study is to explain current state of digital books within post-graduate students' perspectives and to identify post-graduate student's perceptions, attitudes and preferences related to digital books. In this regard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Hu and Zhang (2016) employed the expectation-confirmation model and technology acceptance model (TAM) to investigate Chinese undergraduates’ continuance intentions toward mobile book-reading apps. Bozkurt et al (2016) identified post-graduate students’ perceptions, attitudes, and preferences related to digital books at the academic level. LaMagna et al (2015) examined the various streams within the library and information science literature related to e-book adoption in academic libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hu and Zhang (2016) employed the expectation-confirmation model and technology acceptance model (TAM) to investigate Chinese undergraduates’ continuance intentions toward mobile book-reading apps. Bozkurt et al (2016) identified post-graduate students’ perceptions, attitudes, and preferences related to digital books at the academic level. LaMagna et al (2015) examined the various streams within the library and information science literature related to e-book adoption in academic libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hart dedicated his life to the digitization and distribution of literature from works in the public domain that are free and expired copyright. He started this endeavor in 1971 with the establishment of PG (Bozkurt, Okur & Karadeniz, 2016). E-books, also known as e-texts, are first created in plain text format and distributed as text files.…”
Section: An Overview Of the Concept Of Electronic Booksmentioning
confidence: 99%
“…First, e-books are digital book formats that make the users, the e-books themselves, and the environment (device) interact with each other digitally because they contain hypermedia and interactive elements which are put together simultaneously. Accordingly, the readers will get an e-reading experience, including cognitive, sensorial, and physical interactions (Bozkurt et al, 2016). Second, interactive e-books require the users' active participation in handling the interactive e-books and their elements.…”
Section: Student Perceptions Of Clil-based Critical Readingmentioning
confidence: 99%